Standardization as A Dilemmatic Policy - Suatmo Pantja Putra (Universitas Merdeka Malang, 2016)
Standard language is generally regarded as language well establishe by usage in the speech and writing of educated people. As a product of schooling, this learnt language has, in may societies, come to assume a special place and is looked upon as an authoritative model of correctness and quality and, at its best, perfection. In language conscious speech communities, standard language also serves as a reliable measure of language proficiency which is made use of by people in administrative or educational authority. Language planners and practitioners in particular are charged with the responsibility of upholding this language in its purest forms. Meanwhile, the learning and teaching of standard language have become accepted as an integral part of every national or state-level educational systems long-term obligations. This paper presents the discussion on the inappropriateness of the use of them” standard‟ instead of “standardized” language. It also suggests that planning for language policy within a particular situation inevitably demands taking into account not only multiple social factors and government goals, but also the ways in which these conditions affect language and literary acquisition across segments of the population, otherwise it can be a dilemmatic and problematic policy.